SCIENCE, HEART, AND THE SENSES: A STUDY OF IMAM AL-GHAZALI'S THOUGHT - Ivan Fanani Qomusuddin; Teguh Hariyanto; Sam’un . (STAI Sebelas April Sumedang, 2025)
This study examines the relationship between knowledge, the heart, and the five senses as presented in the classical work Ihya’ ‘Ulum al-Din by Imam Al-Ghazali. In Islamic intellectual tradition, these three elements are often understood as interconnected components in the process of acquiring knowledge. However, Imam Al-Ghazali offers a clear conceptual distinction and an in-depth explanation of the roles and functions of each element, as well as their interrelationship and its impact on a Muslim’s spiritual and social life. The five senses are viewed as the initial means of perceiving external reality, while the heart (qalb) functions as the center of awareness, understanding, and inner judgment. Knowledge, in Al-Ghazali’s perspective, is not limited to rational and empirical understanding but also encompasses inner and spiritual knowledge derived from the purity of the heart. The research method employed in this study is library research, using a content analysis approach. Data were collected through documentation, with Ihya’ ‘Ulum al-Din as the primary source, supported by relevant books and scholarly works as secondary sources. The findings indicate that the five senses, the heart, and knowledge operate synergistically to shape a holistic understanding of human cognition. This synergy enables individuals to acquire knowledge that is not only empirical and rational but also spiritual in nature, thereby contributing positively to moral formation, social life, and spiritual closeness to Allah SWT. Keywords : Science, Heart and Five Senses, Imam Al-Ghazali, Ihya' Ulumudin.